Islamic Da'wah: theory and practice / Sohirin M. Solihin - Haque, Munawar (IIUM Press, 2009)
Da'wah refers to calling or inviting people to embrace Islam. Though not an article of the Islamic Faith, Muslims are urged to be actively engaged in Da'wah activities. The book under review explains, as the title indicates the theory and practice of da'wah and is thus addresse mainly to the Muslims. It is significant addition to books on Da'wah. The aurthor, while teaching Qur'an and sunnah at the Intenational Islamic University Malaysia, is himself involved in da'wah activities including inter-faith dialogues.